‘Would you eat cultured meat?’: Consumers' reactions and attitude formation in Belgium, Portugal and the United Kingdom - Verbeke, Wim (2015)
Cultured meat has evolved froman idea and concept into a realitywith the August 2013 cultured hamburger tasting in London. Still, howconsumers conceive culturedmeat is largely an open question. This study addresses consumers' reactions and attitude formation towards cultured meat through analyzing focus group discussions and online deliberationswith 179 meat consumers from Belgium, Portugal and the United Kingdom. Initial reactions when learning about culturedmeatwere underpinned by feelings of disgust and considerations of unnaturalness. Consumers sawfewdirect personal benefits but they weremore open to perceiving global societal benefits relating to the environment and global food security. Both personal and societal riskswere framed in terms of uncertainties about safety and health, and possible adverse societal consequences dealing with loss of farming and eating traditions and rural livelihoods. Further reflection pertained to skepticism about ‘the inevitable’ scientific progress, concern about risk governance and control, and need for regulation and proper labeling.